2017
DOI: 10.2147/ott.s145776
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between <em>IGF2BP2</em> and <em>PPARG</em> polymorphisms and susceptibility to esophageal squamous-cell carcinomas in the eastern Chinese Han population

Abstract: The aim of this case–control study was to assess whether PPARG and IGF2BP2 polymorphisms confer susceptibility to esophageal squamous-cell carcinoma (ESCC). A total of 507 patients pathologically confirmed for ESCC and 1,496 age-, sex-, and residence-matched healthy individuals were enrolled. The PPARG rs1801282 C>G and rs3856806 C>T and IGF2BP2 rs1470579 A>C and rs4402960 G>T polymorphisms were selected and genotyped by SNPscan genotyping assays. Multivariable logistic analysis suggested that the PPARG rs3856… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…To further investigate such a developing pathway, we profiled the downstream genes of miR-200b through miRWalk, of which IGF2BP2 stood out as a potential target involved in the regulating pathway of ESCC. The underlying rationale here is that IGF2BP2 expression was reported to be upregulated in ESCC (10), which was also verified by the present GEPIA analysis, RT-qPCR, and immunoblotting results. The impact of IGF2BP2 expression on the biological characteristics of ESCC cells was recently reported (23), and our present results of scratch and Transwell assays concur with that result, in displaying that CCAT2 upregulated the expression of IGF2BP2 by adsorbing miR-200b in ESCC cells to promote their migration and invasion capacity.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…To further investigate such a developing pathway, we profiled the downstream genes of miR-200b through miRWalk, of which IGF2BP2 stood out as a potential target involved in the regulating pathway of ESCC. The underlying rationale here is that IGF2BP2 expression was reported to be upregulated in ESCC (10), which was also verified by the present GEPIA analysis, RT-qPCR, and immunoblotting results. The impact of IGF2BP2 expression on the biological characteristics of ESCC cells was recently reported (23), and our present results of scratch and Transwell assays concur with that result, in displaying that CCAT2 upregulated the expression of IGF2BP2 by adsorbing miR-200b in ESCC cells to promote their migration and invasion capacity.…”
Section: Discussionsupporting
confidence: 84%
“…However, whether or how CCAT2 regulates miR-200b in the progression of ESCC remains unknown. Moreover, insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2) is reported to be oncogene, which is highly related to ESCC ( 10 ), and furthermore the abnormal expression of thymidine kinase 1 (TK1) is regarded as an important clinical characteristic in patients with ESCC ( 11 ). As such, it seems plausible that both IGF2BP2 and TK1 are involved in the signaling axis initiated by CCAT2.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the relationship between IGF2BP2 and IGFBP3 SNPs and NSCLC risk, we selected polymorphisms in IGF2BP2 and IGFBP3 gene according to the publications, which were associated with the development of cancer. 12 , 13 , 19 21 …”
Section: Methodsmentioning
confidence: 99%
“…Multivariate logistic analyses have demonstrated that IGF2BP2 rs1470579 and rs4402960 polymorphisms increase the risk of developing esophageal squamous-cell carcinoma [ 78 ]. In contrast, a separate research showed that IGF2BP2 rs1470579 phenotype decreases the risk of developing esophagogastric junction adenocarcinoma in Eastern Chinese Han population [ 79 ].…”
Section: Igf2bp2 and Cancersmentioning
confidence: 99%